2014
DOI: 10.1101/010330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How predator hunting-modes affect prey behaviour: Capture deterrence inDrosophila melanogaster

Abstract: 20!Hunting mode, the distinct set of behavioural strategies that a predator employs while 21! hunting, can be an important determinant of the prey organism's behavioural response. 22!However, few studies have considered how a predator's hunting mode influences anti-23! predatory behaviours of a prey species. Here we document the influence of active hunters 24! (zebra jumping spiders, Salticus scenicus) and ambush predators (Chinese praying 25! mantids, Tenodera aridifolia sinensis) on the capture deterrence an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…For instance, in the presence of mantids, the Drosophila showed similar levels of activity as during the absence of mantids. However, an earlier study demonstrated that they spent more time lifting their abdomens as a signal of vigilance (Parigi et al 2014). Unless more time spent lifting led to higher energy expenditure, Elliott et al (a) Total number (mean ± SE) of offspring emerged, and (b) development time (mean ± SE) for the stock (stock population captive for ∼900 generations; grey symbols), control-evolved (wild population held captive within a cage without mantid predators for ∼1000 generations; black symbols), and predator-evolved (wild population held captive within a cage with mantid predators for ∼1000 generations; white symbols) populations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, in the presence of mantids, the Drosophila showed similar levels of activity as during the absence of mantids. However, an earlier study demonstrated that they spent more time lifting their abdomens as a signal of vigilance (Parigi et al 2014). Unless more time spent lifting led to higher energy expenditure, Elliott et al (a) Total number (mean ± SE) of offspring emerged, and (b) development time (mean ± SE) for the stock (stock population captive for ∼900 generations; grey symbols), control-evolved (wild population held captive within a cage without mantid predators for ∼1000 generations; black symbols), and predator-evolved (wild population held captive within a cage with mantid predators for ∼1000 generations; white symbols) populations.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioural response of Drosophila to Tenodera sinensis was studied in detail by Parigi et al (2014), who observed that Drosophila increased abdominal bobbing in response to the mantid predator. There was a bimodal response in terms of the time spent grooming and the time spent walking, with most individuals spending more time grooming and walking, and others spending less time (Parigi et al 2014).…”
Section: Fear Behavioural Experimentsmentioning
confidence: 99%
See 3 more Smart Citations